Efektifitas Kinerja Pentoksifilin Terhadap Kualitas dan Integritas Membran Plasma Utuh pada Sperma Sapi Bali Hasil Pemisahan dengan Menggunakan Albumin - Enny Yuliani; Adji Santoso Dradjat; Chairussyuhur Arman; Rodiah Rodiah (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2015)
The purpose of this research was to determine the effect of Pentoxyfilline in maintaining the quality (motility, viability, morphology and plasma membrane intact) of Bali bull spermatozoa separated with albumine. A Completely Random Block Design was used in this study with two main factors (upper layer and bottom layer), diluents with four doses of pentoxyfilline (0, 15, 20 and 25 Î¼M) with six replications. Evaluation of spermatozoa was performed by characterizing motility, viability, morphology, plasma membrane intact. Result of the study showed that the effect of four doses pentoxyfilline on the quality of Bali bull spermatozoa was non significant (p>0,05). However, the addition of 25Î¼M pentoxyfilline was found to give the best effect compared to 15 Î¼M, 20 Î¼M and control. Result of the study also indicated that spermatozoa separated in the upper layer was signifiqantly higher (p<0,01) than that of separated in the bottom layer with the average motility, viability, morfology and plasma membrane intact was 66,67,80,50, 6,71 and 65,61% respectively.